Independency Models of Nursing self-care for Ischemic Stroke Patient - Fery Agusman Motuho Mendrofa; Chatarina U. Wahyuni; Nursalam Nursalam; Hasan Machfoed; Kuntoro Kuntoro; Hari Basuki Notobroto; Rachmad Hargono; Bagus Widjonarko (International Journal of Public Health Science (IJPHS), 2015)
Stroke injury such as physical and psychological disorders was required assistance such as the community, nursing professional and family. Family and social factors play an important role in independence strokes such as support family members provide encouragement for self care.The objective of aim the study wasto assess indicator of self care and model family support related self care. A cross-sectional survey research design was used. Data was collected with interviews by home visited method. Data were analyzed with confirmatory analysis for determined of validity and reliability indicator, models analyzed by SEM (Structural Equation Model).Family support such as information, instrumental, reward and emotion were valid indicator for family support. Self care indicators such as eat, bath, titivate, dress, defecating, urination and transfer to building of self-care. Indicators of eating, bathing, titivate, dress, defecate, urination, and transfer is an indicator for self care. It could be concluded that eating, bathing, ornate, dress, and the transfer is valid and reliable. Model showed that self-care needs were improved of self-carepatients with through family support.